MENCIPTAKAN PEMBIAYAAN PENDIDIKAN SEKOLAH/MADRASAH SECARA MANDIRI DALAM BINGKAI MANAJEMEN BERBASIS SEKOLAH/MADRASAH. - Zaedun Na'im (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2023)
This paper is to explore the importance of managing education financing in order to improve the quality or quality of education in educational institutions, but in managing education financing it has not yet implemented and optimized a school- or madrasah-based management model so that it has not shown independence in the development of education in schools/ madrasas through the utilization of Education financing. Therefore, in this case, this paper needs to be raised with the aim of analyzing in depth how to implement educational financing management within the framework of school or madrasah-based management in realizing the independence of educational institutions. The method used in this paper uses the Research library approach. The results of the study concluded that financial or financial management by implementing school-based management will create school/madrasah independence in regulating the direction of educational development through the use of school finance or funding. And the efforts that can be made by schools/madrasas to obtain funding do not only depend on the central or regional government, but can optimize the school's internal circle or the surrounding community.